Anti-Trichomonas gallinae activity of essential oils and main compounds from Lamiaceae and Asteraceae plants - Bailén, María; Díaz-Castellanos, Irene; Azami-Conesa, Iris; Alonso Fernández, Sara; Martínez-Díaz, Rafael A.; Navarro-Rocha, Juliana; Gómez-Muñoz, María Teresa; González-Coloma, Azucena (Frontiers in Veterinary Science, 2022)
Trichomonas gallinae is a flagellated protozoan that parasitizes the upper digestive tract of various bird species and causes avian trichomonosis. The emergence of resistant strains to the standard treatment, based on nitroimidazoles, increases the need to find alternative therapies. In this study, 36 essential oils (EOs) from Lamiaceae and Asteraceae plant families were tested against T. gallinae trophozoites using the 3-(4,5-dimethylthiazol-2-yl-)-2,5-dipheniltetrazolium bromide (MTT) reduction assay. Among them, EOs from distinct species of Lamiaceae, including the genera Lavandula, Salvia, Thymus, Origanum, and Satureja were the ones reporting better anti-trichomonal activity, and were selected for further analysis. The chemical composition of the selected EOs was determined by gas chromatography followed by mass spectrometry and 19 pure compounds were tested against the protozoa, according to their higher abundance in the active EOs. Pure compounds which displayed the highest activity against T. gallinae trophozoites, ordered by highest to lowest activity, were α and β-thujones, camphene, β-pinene, linalyl acetate, thymol, 4-terpineol, γ-terpinene, α-pinene, ρ-cymene, D-fenchone and β-caryophyllene. A dose dependent effect was observed in most of the EOs and pure compounds tested. The toxicity test carried out in eukaryotic cell cultures with the anti-trichomonal active pure compounds showed that, β-caryophyllene, camphene, α-pinene and β-pinene were slightly toxic for Vero cells, and the selectivity index was calculated. Based in the anti-trichomonal activity and the absence of cytotoxicity results, natural products from Lamiaceae plants could be useful as alternative therapy against avian trichomonosis, mainly linalyl acetate, thymol, 4-terpinenol, γ-terpinene, ρ-cymene and D-fenchone.